Inventory Of Araceae Family At Faculty Of Science And Technology Sunan Gunung Djati State Islamic University - Nuna Syabarina Novia N. M Novia N. M; Nur Hanifatuz Zahra; Ateng Supriatna (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
The Araceae family is a seedling plant that is often utilized for ornamental purposes. The aim of this research is to inventory Araceae plants in the area surrounding the Faculty of Science and Technology at UIN Sunan Gunung Djati Bandung. The method used is a descriptive method involving data collection and literature review. A total of 5 species from 4 different genera of Araceae plants were found, namely Syngonium podophyllum, Dieffenbachia sp., Spathiphyllum cochlearispathum, Aglaonema nitidum, and Aglaonema crispum. Araceae plants have several potential uses as food, decoration, medicine, and vegetables. Famili Araceae merupakan tumbuhan semai yang sering dimanfaatkan untuk dijadikan tanaman hias. Tujuan dari penelitian ini adalah untuk menginventarisasi tumbuhan Araceae di kawasan sekitar Fakultas Sains dan Teknologi UIN Sunan Gunung Djati Bandung. Metode yang digunakan adalah metode deskriptif dengan pengumpulan data dan studi literatur. Jumlah tumbuhan Araceae yang ditemukan sebanyak 5 spesies dari 4 genus yang berbeda-beda, yaitu Syngonium podophyllum, Dieffenbachia sp., Spathiphyllum cochlearispathum, Aglaonema nitidum dan Aglaonema crispum. Tumbuhan Araceae memiliki beberapa potensi manfaat sebagai makanan, hiasan, obat, dan sayuran.